Establishing intergenerational relationships in unlikely collaborative educational contexts - Pedro Moreno Abellán; Silvia Martínez de Miguel López; Juan Antonio Salmerón Aroca (Risks, 2022)
This work presents a project called "ESium Project", whose main objective is to create new spaces for social participation and a relationship between two different age groups: the young Social Education students and the elderly. It has a double purpose: to promote that reciprocal space for cooperation and interaction in a way that avoids the risk of disengagement and to promote a professional perspective. Target students will become future professionals who will also work with the elderly collective. Furthermore, a research-action method aims to make the participants protagonists of the educational actions that are carried out by using qualitative techniques as essential strategies for the work of collectives. Not only do the results regard the intergenerational stereotypes, they also show the assessment of the satisfaction by the involved participants, the international acknowledgement of the educational activity developed, and the possibility to use this in other contexts. In this way, it can be concluded that there is a need to tackle intergenerationally in teacher education from a wide-open inclusive perspective to take advantage of senior talent and innovation.
Keywords: 330; education; intergenerational relationships; risk; teachers